Analisis Profil dan Strategi Pengembangan Usaha Ternak Sapi Kurban di Medan Krio Sunggal - Zainarti Zainarti; Amanda Mutiara Hasibuan; Yauma Afriyanti; Imel Santika; Widya Anggraini (Zoologi: Jurnal Ilmu Peternakan, Ilmu Perikanan, Ilmu Kedokteran Hewan, 2025)
This research uses a quantitative method and focuses on a cattle breeder named Nur Amin, aged 53, who has been raising sacrificial cattle since 2022 in Medan Krio Village, Sunggal Subdistrict. The purpose of this study is to analyze the breeder’s profile and the strategies implemented in developing the sacrificial cattle business. The farm consists of 12 cows—10 males and 2 females—mainly of Simmental and Brahman breeds. The study found that feed fermentation and regular vitamin administration play significant roles in improving cattle growth and health. In addition, regular stable hygiene and the application of artificial insemination are key factors in livestock management. Although no major obstacles have been encountered, limited promotion and market access remain challenges for business expansion. The research also emphasizes the importance of treating cattle farming as a primary business, not just a side activity. The inclusion of Islamic principles and religious texts reinforces that this business aligns with Islamic values, especially in providing halal and high-quality sacrificial animals for religious rites.